2015
DOI: 10.1108/nlw-06-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Drug information seeking behaviours of health care professionals in Iran

Abstract: Purpose – The purpose of this paper is to list the resources that Iranian health-care professionals used to access drug-related information, to know the features and types of drug information resources which were much more important for health-care professionals, the problems they encountered in seeking drug information and the way they organized and re-found the information that they had retrieved. Drug-related queries are one of the most common types of questions in medical settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Another study in Canadian universities showed a widespread use of smartphones and tablets for clinical purposes . These tools are also becoming popular in developing countries for accessing scientific databases and drug references, Web browsing, communication purposes and for assisting better clinical decision making …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Canadian universities showed a widespread use of smartphones and tablets for clinical purposes . These tools are also becoming popular in developing countries for accessing scientific databases and drug references, Web browsing, communication purposes and for assisting better clinical decision making …”
Section: Introductionmentioning
confidence: 99%
“…9 These tools are also becoming popular in developing countries for accessing scientific databases and drug references, Web browsing, communication purposes and for assisting better clinical decision making. 4,10 The advantages of using mobile technologies in health care are already visible when physicians adopt and use these tools in medical settings. 2 In order to encourage health care professionals to use smartphones or other mobile technologies in daily clinical activities, this is helpful to know which factors affect their acceptance for professional purposes.…”
Section: Introductionmentioning
confidence: 99%
“…To find answers to these clinical questions, physicians refer to different types of information sources. For drug information needs, sources used by physicians include textbooks, drug manuals, drug leaflets, journals (Tahamtan, I., 2015), clinical practice guidelines, electronic references, e.g.…”
Section: Finding Evidence To Answer Clinical Questionsmentioning
confidence: 99%
“…To reiterate, through existing literature, we have learned different aspects of physicians' clinical information-seeking behavior and practices including different information sources they use for seeking information (Tahamtan, I., 2015), factors influencing their information-seeking practices as well as clinical decision-making for drug prescriptions (Rahmner et al, 2008;Zhang et al, 2019), and current status and attitudes of physicians regarding critical appraisal (Wood et al, 2022). However, we still lack complete comprehension of the current process of physicians' evidence-based information-seeking, critical appraisal, and clinical decision-making for applying that information in the context of actual practice settings.…”
Section: Research Questionmentioning
confidence: 99%